A renovation works for space expansion of an office room / Muhammad Ashraf Ahmad Jasmani - Ahmad Jasmani, Muhammad Ashraf (Universiti Teknologi MARA, Perak, 2021)
Renovation (also known as remodelling) is the process of repairing or replacing a broken, damaged, or out-of-date structure. Commercial and residential renovations are both common. Furthermore, refurbishment can relate to creating something new or bringing something back to life, and it can be used in social circumstances. A community, for example, can be renovated if it is fortified and revitalised. Many people modify their homes to give them a fresh look or to allow another person to live in them. Home renovations are popular among builders because they provide a steady source of revenue. Homeowners frequently modify their properties in order to boost their resale value and profit when they sell. Additionally, homeowners may choose to make their home more energy efficient, environmentally friendly, or sustainable, which may necessitate some renovation work. Alternatively, for aesthetic or comfort reasons, a homeowner own preferences and demands may change over time, necessitating a makeover.